Income gradient of pharmaceutical panic buying at the outbreak of the COVID-19 pandemic - Petér S. Elek; Anikó Bíró; Petra Fadgyas-Freyler (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
We analyse the timing, magnitude and income dependence of pharmaceutical panic buying around the outbreak of the COVID-19 pandemic in Hungary. We use district-level monthly and daily administrative data on detailed categories of pharmaceutical purchases, merge them to income statistics and estimate multilevel panel models. Our main results are as follows. First, the days of therapy (DOT) of pharmaceutical purchases increased by more than 30% in March 2020, when major lockdown measures were announced. This pattern holds for almost all categories of pharmaceuticals. Second, shortly after the panic reactions, the aggregate amount of pharmaceutical purchases returned to their pre-shock levels, however, the frequency of pharmacy visits decreased. Third, the panic buying reaction was significantly stronger in richer geographical areas, where - according to the daily data - people also reacted earlier to the pandemic-related news. Overall, the results suggest that panic buying of pharmaceuticals can have detrimental effects on vulnerable populations.
Keywords: I12; I14; 330; COVID-19; inequality; panic buying; pharmaceutical demand